Sediment Transport Analysis Of Teluk Kepayang Using Hec-Ras - Rozali, Nor Shawani Mohamad (Universiti Sains Malaysia, 2022)
In this investigation, an Acoustic Doppler Current Profiler, or ADCP, was utilised in order to acquire both the cross section at the river's bottom and the width of the river that was being investigated. Sand and gravel can be obtained from rivers in the vast majority of tropical countries with little effort and little need for processing based on size grading. Sand is the primary material that is utilised in the building and construction sector, and demand is growing as a result of the industry's rapid development. However, the amount of sand, gravel, and other materials that are extracted shouldn't go above and beyond what can be produced naturally. An unsustainable amount of sand removal can throw off the natural equilibrium of river channels. The main objective in this study is to simulate the 2.6 kilometer Teluk Kepayang Sungai Perak using HEC-RAS to obtain cross-sectional graphs that show sediment transport events. In this study, HEC-RAS 1D sediment transport was utilised to study the four different lines that were chosen. Line 4, which is located in the upstream portion of the river, Line 3, Line 2, and Line 1 are all located downstream in the area of Teluk Kepayang. The lines are labelled with their respective locations. At the bottom of the river in Teluk Kepayang, the difference in height caused by sediment erosion as a result of sediment transport is, on average, 1.1827 metres along Line 4, 0.8781 metres along Line 3, 1.1159 metres along Line 2, and 1.0167 metres along Line 1. The water level drops by fifteen percent as the HEC-RAS simulation is run in the opposite direction, from upstream to downstream. In addition, HEC-RAS findings determined that the river was eroding from upstream to downstream, based on simulations of four different lines. Researchers from all over the world have made use of the HEC-RAS software in order to assist them in analysing river channel flows that can simulate rivers.